Cooperation Of Preschool Educational Organization With The Family In Developing Creative Abilities In Preschool Children - Qurbanova, Xusnidaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article analyzes the role and significance of the collaboration between preschool educational institutions (PEI) and families in developing creative abilities in preschool children. It discusses the impact of the cooperation between families and PEIs on the enhancement of children's creative potential and examines effective methods and approaches.